Penerapan E-Government dalam Pelayanan Publik di Kota Jayapura - Bonefasius Bao; Hendrik Vallen Ayomi; Hendry Bakri; Peliman Ndibau (Journal on Education, 2023)
Acceleration of improving public services using a digitalization approach in the industrial era 4.0 is something that is no longer commonplace. The government as a public service provider is expected to be able to take advantage of these technological advances, to increase its ability to process, manage, distribute and distribute information and public services. The implementation of this electronic-based government is carried out to improve the quality of public services that are effective, efficient, transparent and accountable. As a barometer of governance in Papua Province, the City of Jayapura is expected to be a role model in e-Government-based public service governance. Therefore, this study aims to describe the implementation of e-Government in relation to openness of public services in Jayapura City. The research methodology used in this research is descriptive qualitative with data collection techniques through in-depth interviews. Data analysis used in this study includes data collection, data presentation, data reduction, and drawing conclusions. The results of this study indicate that the Jayapura city government has made efforts to utilize electronic-based public services, although it has not been maximized.